What the Bible is all about for young explorers : based on the best-selling classic by Henrietta Mears - Blankenbaker, Frances; Choun, Robert J.; Yasuda, Chizuko; Mears, Henrietta C. (Henrietta Cornelia), 1890-1963. (Ventura, Calif., U.S.A. : Regal Books, 1986)
A discussion of the origin, significance, and contents of the Bible, with a book-by-book analysis of events and timelines, photographs, and maps to pinpoint when and where they happened.
"This special version--for young explorers--is written to help children and young people discover for themselves what the Bible is all about"--P. [3].
Keywords: Bible -- Juvenile literature; Bible